A Synthesis of Research on Informational Text Reading Interventions for Elementary Students With Learning Disabilities. (May 2016) - Ciullo, Stephen; Lo, Yu-Ling Sabrina; Wanzek, Jeanne; Reed, Deborah K.
This research synthesis was conducted to understand the effectiveness of interventions designed to improve learning from informational text for students with learning disabilities in elementary school (K–5). The authors identified 18 studies through a comprehensive search. The interventions were evaluated to determine treatment effects and to understand implementation and methodological variables that influenced outcomes. Moderate to large effect sizes on researcher-developed measures for cognitive strategy interventions were reported. Interventions that utilized graphic organizers as study guides to support social studies learning were also associated with improved outcomes. The findings are considered within the context of limited implementation of standardized measures. The authors extend findings from previous research by reporting a paucity of interventions to enhance higher-level cognitive and comprehension skills. The majority of reviewed studies targeted fact acquisition and main idea identification, and overall encouraging findings were noted for these skills. Implications for future research are discussed.